Pendekatan terapi ABA dan terapi okupasi dalam mengembangkan kemampuan sosial pada anak autisme - Qolbi, Delima Dawaul (Maliki Interdisciplinary Journal, 2025)
This study discusses the application of Applied Behavior Analysis (ABA) and occupational therapy in developing the social skills of children with autism spectrum disorders in special schools. ABA is an approach based on Operant Conditioning theory that focuses on behavioral change through structured procedures, positive reinforcement, and data analysis to improve compliance, eye contact, and social skills in children. Meanwhile, occupational therapy emphasizes the development of children's independence through meaningful daily activities, such as dressing, socializing, and performing vocational activities. The results of interviews and observations show that these two therapies complement each other in helping autistic children develop social skills, improve their quality of life, and prepare them to be more adaptive in their environment. The similarities between the two lie in the use of structured, repetitive methods and individual evaluation, while the differences lie in the scope of the objectives and focus of the intervention. These findings emphasize the importance of simultaneously applying ABA and occupational therapy to support the development of autistic children